Features of glycemic variations in drug naïve type 2 diabetic patients with different HbA1c values - Li, Feng-fei; Liu, Bing-li; Yan, Reng-na; Zhu, Hong-hong; Zhou, Pei-hua; Li, Hui-qin; Su, Xiao-fei; Wu, Jin-dan; Zhang, Dan-feng; Ye, Lei; Ma, Jian-hua (Scientific reports, 2017)
To define the features of glycemic variations in drug naïve type 2 diabetic (T2D) patients with different HbA 1c values using continuous glucose monitoring (CGM), a total of 195 drug naïve T2D patients were admitted. The subjects were divided into the following groups: lower HbA 1c values (≤8%), moderate HbA 1c values (>8% and ≤10%), and higher HbA 1c values (>10%). The patients underwent oral glucose tolerance tests and were then subjected to 3-day CGM. The primary endpoint was the differences in the 24-hr mean amplitude of glycemic excursions (MAGE) in patients with different HbA 1c values. Patients with higher HbA 1c values had larger MAGEs than those in the moderate and lower groups (7.44 ± 3.00 vs. 6.30 ± 2.38, P < 0.05, 7.44 ± 3.00 vs. 5.20 ± 2.35, P < 0.01, respectively). The 24-hr mean glucose concentrations increased incrementally in the patients with lower, moderate and higher HbA 1c values. Moreover, the patients with higher HbA 1c values exhibited higher peak glucose concentrations and prolongation in the time to peak glucose. Patients with higher HbA 1c values had larger MAGE compared with those with lower and moderate HbA 1c values. Our data indicated patients with higher HbA 1c values should receive special therapy aimed at reducing the larger glycemic variations.